Network congestion control at the application layer - Adamczyk, Paul
Application-layer protocols play a special role in network programming. Typical programmers are more familiar with them and more likely to implement them. Well-designed application-layer protocols follow many patterns that improve the performance of applications using these protocols. We present a subset of these patterns that focuses on the congestion control at the application layer.